EFFECT OF STREPTOCOCCUS SUIS VACCINES WITH DIFFERENT ADJUVANTS ON PRIMARY ANTIBODY TITERS IN MICE DETECTED BY ELISA TEST USING SUPERNATAN ANTIGENS - Jovan Takasi Amadeo Hutapea; I Nengah Kerta Besung; I Gusti Ngurah Sudisma; Ni Ketut Suwiti; I Gusti Ngurah Kade Mahardika (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Streptococcus suis is a zoonotic pathogen that causes infection in pigs and has the potential to be transmitted to humans. One of the effective strategies in the prevention of this infection is vaccination, where adjuvant selection plays an important role in enhancing the immune response. This study aimed to evaluate the effect of using different adjuvants in S. suis vaccine on primary antibody titers in mice, measured using ELISA assay with supernatant antigen. This study used a factorial complete randomized design with two factors, namely adjuvant type and observation time. Serum samples were collected weekly for four weeks for antibody titer analysis. The results showed that the vaccine with Montanide ISA 201 VG adjuvant produced significantly higher antibody titers compared to the vaccine using Montanide Gel 01 adjuvant and the control group (P < 0.05). The conclusion of this study is that Montanide ISA 201 VG adjuvant is more effective in enhancing primary immune responses than Montanide Gel 01, so it has the potential to be used in the development of a more optimal S. suis vaccine.